2020
DOI: 10.1002/cche.10382
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional in vitro bioactive properties: Antioxidant, antidiabetic, and antihypertensive of protein hydrolyzates from tarwi (Lupinus mutabilis Sweet) obtained by enzymatic biotransformation

Abstract: Background and objectives Tarwi is a legume that grows in the Andean region of Peru. This grain is characterized by having a high protein content (~42%). In order to generate added‐value products from this resource, the possibility of obtaining tarwi protein hydrolyzates (TPH) with in vitro bioactive properties was evaluated using Alcalase, Neutrase, and Flavourzyme enzymes, acting alone or in combination for up to 240 min. The in vitro evaluated properties were as follows: antioxidant (ABTS assay), antidiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 35 publications
0
24
0
9
Order By: Relevance
“…The quantity of HA was calculated by chromatographic analysis (at 228 nm) according to Chirinos et al . (2021). ACE inhibition was expressed as percentage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of HA was calculated by chromatographic analysis (at 228 nm) according to Chirinos et al . (2021). ACE inhibition was expressed as percentage.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the nutritional benefits of the seed, it has a high alkaloid content, so before use, it must be de‐bitterised by soaking with water and heat treatment. Thus, recently tarwi has been explored as a potential source for obtaining protein hydrolysates with multifunctional properties: antioxidant, antidiabetic and antihypertensive, resorting to hydrolysis with commercial enzymes of microbial origin, generating very encouraging results (Chirinos et al ., 2021). Research carried out on tarwi protein hydrolysates have confirmed the antioxidant and inhibition of hepatic gluconeogenesis effects (Intiquilla et al ., 2018; Muñoz et al ., 2018), but studies on the structure and nature (size, type and sequence of amino acids and hydrophobicity) of its bioactive peptides are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The higher ABTS •+ radical scavenging capacity of the hydrolyzates obtained after the combined action of three enzymes (pepsin, pancreatin, and Alcalase) in comparison with those obtained only by pepsin could be due to the higher efficiency of the hydrolytic process. Thus, Chirinos et al reported the higher antioxidant activity of Alcalase-Flavourzyme hydrolyzates from tarwi ( Lupinus mutabilis ) than that of Alcalase hydrolyzates [ 37 ]. Similarly, other works have found higher ABTS •+ radical scavenging capacity of soybean [ 38 ], cañihua ( Chenopodium pallidicaule ) [ 39 ], and kiwicha ( Amaranthus caudatus ) [ 40 ] protein hydrolyzates using Alcalase combinations with other enzymes compared with only Alcalase.…”
Section: Resultsmentioning
confidence: 99%
“…Although this value was higher than that measured for Captopril, used as standard in this assay (6.81 µg/mL), it was much lower than those reported for hydrolyzates from other plant proteins. As examples, Alcalase-hydrolyzates of Lupinus angustifolius protein showed IC 50 values ranged from 100–210 µg protein/mL [ 45 ], and the tarwi protein hydrolyzate by an Alcalase-Neutrase combination for 180 min showed an IC 50 value of 110 µg protein/mL [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antihypertensive activity of wheat germ was due to the ACE inhibitory peptide produced after hydrolysis of protein ( 75 ), and the dominant peptide of ACE inhibitory peptide was Ile-Val-Tyr (Ivy) ( 76 ). The activity of ACE obtained by different proteolytic methods was various ( 77 , 78 ). The activity of ACE inhibitory peptide in wheat germ enzymatic hydrolysate obtained by Qu et al ( 19 ) was 65.9%, while the activity of ACE inhibitory peptide in wheat germ enzymatic hydrolysate pretreated by Jia et al ( 41 ) ultrasonic increased by 21.0-40.7%.…”
Section: The Biological Activity Of Wheat Germ Peptidesmentioning
confidence: 99%